2D particle-in-cell simulations of geometrically asymmetric low-pressure capacitive RF plasmas driven by tailored voltage waveforms. (19th May 2021) - Wang, Li; Hartmann, Peter; Donkó, Zoltán; Song, Yuan-Hong; Schulze, Julian
Abstract: The effects of the simultaneous presence of two different types of plasma asymmetry, viz, geometric and electrical, on low-pressure capacitively coupled argon discharges are studied by 2D3V graphics-processing-unit-based particle-in-cell/Monte Carlo simulations. The geometric asymmetry originates from the different powered vs grounded electrode surface areas, while the electrical asymmetry is established by applying peaks/valleys and sawtooth-up/-down driving voltage waveforms. While in geometrically symmetric discharges, the peaks ↔ valleys and the sawtooth-down ↔ sawtooth-up switching of the waveforms is equivalent to exchanging the powered and grounded electrodes, this transformation is violated when the geometric symmetry is broken. Under such conditions, the plasma characteristics and the DC self-bias generation behave differently, compared to the geometrically symmetric case. This leads to different sheath dynamics and, therefore, strongly influences the electron power absorption dynamics. For identical peak-to-peak voltages, the plasma density obtained for such tailored voltage waveforms is found to be higher compared to the classical single-frequency waveform case. Reduced plasma densities are found in the valleys- and sawtooth-down waveform cases, compared to the peaks- and sawtooth-up waveforms. By including realistic energy and material-dependent secondary electron emission (SEE) coefficients in the simulations, the electron-induced SEE is found to be reduced in the valleys- and sawtooth-down waveform cases, which explains the behaviour of the plasma density. Using such tailored waveforms in geometrically asymmetric discharges is also found to lead to the formation of different charged particle energy distributions at the boundary surfaces, compared to those in geometrically symmetric plasma sources.